2019
DOI: 10.1093/ibd/izz020
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing of Ulcerative Colitis–associated Colorectal Cancer Based on Novel Somatic Mutations Identified in Chinese Patients

Abstract: Background Carcinogenesis is a severe consequence of chronic ulcerative colitis. We investigated the somatic mutations and pathway alterations in ulcerative colitis–associated colorectal cancer (CRC) in Chinese patients compared with sporadic CRCs to reveal potential therapeutic targets in ulcerative colitis–associated CRC. Methods Whole exome sequencing was performed on archival tumor tissues and paired adjacent nondysplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…A previous study reported that somatic mutations and altered pathways are one of the reasons why UC turns into cancer [ 30 ]. Besides, Yan et al [ 9 ] found that COL6A3 referred to apoptosis, and the phosphatidylinositol 3-kinase/Akt pathway is associated with nonsilent recurrent somatic mutations in UC. COL3A1 is a profibrogenic extracellular matrix gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that somatic mutations and altered pathways are one of the reasons why UC turns into cancer [ 30 ]. Besides, Yan et al [ 9 ] found that COL6A3 referred to apoptosis, and the phosphatidylinositol 3-kinase/Akt pathway is associated with nonsilent recurrent somatic mutations in UC. COL3A1 is a profibrogenic extracellular matrix gene.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 8 ] found several genes associated with the development of UC, such as MMP1 , REG1A , and AQP8 . Yan et al [ 9 ] found 11 mutated genes differentially expressed in UC samples, such as APC , APOB , MECP2 , NCOR2 , and USP48 . All these reports suggested that feature genes might play an important role in the diagnosis of UC.…”
Section: Introductionmentioning
confidence: 99%
“…CRC is a major long-term serious complication in patients with UC (22)(23)(24). Previous studies have shown that the main area of colon cancer incidence (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Yang VW and Liu Y found that the deletion of KLF4 causes genetic instability, which in turn leads to the progress of CAC (36). The mutation of APOB gene in CRC associated with ulcerative colitis was found by whole exon sequencing, and there was signi cant difference between ulcerative colitis associated CRC and scattered CRC (37). CD44 is an adhesion and anti-apoptotic molecule that is highly expressed in colon cancer (38).…”
Section: Discussionmentioning
confidence: 99%